Subdermal Flexible Solar Cell Arrays for Powering Medical Electronic Implants. Issue 13 (3rd May 2016) - Song, Kwangsun; Han, Jung Hyun; Lim, Taehoon; Kim, Namyun; Shin, Sungho; Kim, Juho; Choo, Hyuck; Jeong, Sungho; Kim, Yong‐Chul; Wang, Zhong Lin; Lee, Jongho
Abstract : A subdermally implantable flexible photovoltatic (IPV) device is proposed for supplying sustainable electric power to in vivo medical implants. Electric properties of the implanted IPV device are characterized in live animal models. Feasibility of this strategy is demonstrated by operating a flexible pacemaker with the subdermal IPV device which generates DC electric power of ≈647 μW under the skin.